Identification of Pelomyxa palustris Endosymbionts - Gutiérrez, Gabriel; Chistyakova, Ludmila V; Villalobo, Eduardo; Kostygov, Alexei Y; Frolov, Alexander O (Protist, 2017)
Pelomyxa palustris is a giant anaerobic/microaerobic amoeba, characterized by a number of exceptional cytological and physiological features, among them the presumed absence of energy producing organelles and the presence of endosymbiotic bacteria. These endosymbionts have been previously distinguished as: a large rectangular-shaped Gram-variable rod with a central cleft; a slender Gram-negative rod; and a slender Gram-positive rod. Using DNA extracted from P. palustris cysts, we have obtained three SSU rRNA gene sequences. We have determined that these sequences are affiliated to three different prokaryotic genera: Methanosaeta (a methanogenic archaea), Syntrophorhabdus (a syntrophic Gram-negative bacteria) and Rhodococcus (an aerobic chemoorganotrophic Gram-positive bacteria). To our knowledge, it is the first time that Syntrophorhabdus has been described as an endosymbiont in association with a methanogen. Strikingly, no traces of Methanobacterium formicicum could be detected, despite this methanogen had allegedly been isolated from trophozoites of P. palustris. It seems that the host and the endosymbionts have established a multipartite syntrophic consortium resembling to some extent those found in sewage treatment plants.
Keywords: autofluorescence; sekvenční analýza RNA; FISH; SSU rRNA; amoeba.; RNA, Ribosomal, 16S; bakteriální RNA; endosymbiosis; Methanosarcinales; RNA, Archaeal; Symbiosis; Phylogeny; Deltaproteobacteria; RNA, Bacterial; Archamoebae; Methane; Rhodococcus; symbióza; fylogeneze; Sequence Analysis, RNA; RNA ribozomální 16S; archeální RNA